How Well Is Maine Doing? Comparing Well-Being across Maine Counties - Daley, Angela; Crawley, Andrew; Rahman, Muntasir; Demosthenes, Jake; Lyons, Erin (Maine Policy Review, 2018)
Maine has experienced major challenges over the last decade including recession, stagnant recovery, and industrial and population decline. But by some measures, Maine is still seen as one of the best in the United States for well-being. In this paper, we critique the notion of what well-being is and how it is measured. Based on the Organisation for Economic Co-operation and Development’s Better Life Initiative, we then propose and construct an index to compare well-being across Maine counties. Our work gives new insights on the types of challenges counties are facing and provides policymakers a new way of empirically understanding these problems.
Keywords: Well-Being; Multidimensionality; Better Life Index; Maine Counties